Pemanfaatan Ruang Terbuka Hijau Publik di Permukiman Kecamatan Rappocini Kota Makassar - Dwi Uthari Novrina; Shirly Wunas; Venny Veronica Natalia (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Public green open spaces as space for social interaction, not only as physical needs but also expected to connect all members of the residents community in the settlement area regardless of social background, economic, and cultural. Rappocini district is an integrated residential area in ±923 Ha land. This district has various types of public green open spaces, i.e. five units of public parks and three units of public fields. Nevertheless, those all public spaces are not in best condition whether in functional and physical appereance. This research aims to identify the condition and availability of public green open spaces function. It also identifies the characteristics of people who visited public green open spaces in Rappocini District. This study used qualitative, quantitative and comparative approaches. The results of this research are most of the green public space services already fulfill the standard but they still need improvement in physical condition and maintenance.